Analisis Musikal dan Non-Musikal pada Perjamuan Kudus Gereja Advent Bandar Lampung - Debora Trefy Nicolaas; Erizal Barnawi; Bian Pamungkas (Grenek: Jurnal Seni Musik, 2025)
The Holy Communion is held as a reminder of Jesus' death on the Cross to redeem humans from sin. This study uses a descriptive qualitative method to determine the Musical and Non-Musical Analysis found in the Holy Communion at the Bukit Kemiling Permai Adventist Church. Data were received through observation, interviews, and documentation and processed using musical and non-musical analysis theories. The Holy Communion song "Betapa S'nang Aku Kabarkan" consists of an intro, verse, chorus, and outro, has 2 phrase forms, and 4 motifs, with a 6/8 time signature with a tempo of 120 BPM. "Salib Di Bukit Golgota" consists of a chorus, verse and outro, has 5 motifs and 2 phrases, with a 3/4 time signature and a tempo of 70 BPM. "Mengapa Darah-Mu, Yesus" with a chorus, verse and outro, has 4 motifs and 2 phrases, a 3/4 time signature and a tempo of 60 BPM. “Pada-Mu Allah Ku Puji” consists of an intro and verse, has 3 motifs and 2 phrases, 4/4 time signature with a tempo of 80 BPM. This research was conducted at the Bukit Kemiling Permai Adventist Church, with the support of the Church Council and Congregation, taking place at night and during the day, the musicians do not have special provisions, the costumes used are predominantly white and dark.